2009
DOI: 10.1371/journal.pone.0006360
|View full text |Cite
|
Sign up to set email alerts
|

Social Stigma and Knowledge of Tuberculosis and HIV among Patients with Both Diseases in Thailand

Abstract: IntroductionDisease-related stigma and knowledge are believed to be associated with patients' willingness to seek treatment and adherence to treatment. HIV-associated tuberculosis (TB) presents unique challenges, because TB and HIV are both medically complex and stigmatizing diseases. In Thailand, we assessed knowledge and beliefs about these diseases among HIV-infected TB patients.MethodsWe prospectively interviewed and examined HIV-infected TB patients from three provinces and one national referral hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 24 publications
7
39
1
4
Order By: Relevance
“…These indicators included``discriminated against while eating meals with family members,''``neglected by family members,''`n eglected by neighbors,''``neglected in the workplace,'' and``facing problems in taking part in social programs'' and were experienced by 51.4z, 15.4z, 45.9z, 61.9z, and 79.5z of patients, respectively. A study conducted in Thailand considered similar indicators and found that approximately 40.0z of patients could not eat meals with their families (15), which was a similar proportion to that observed in the present study. Another study conducted in Nepal found that 43.3z of TB patients were neglected by others, and 36.7z were asked to stay away from work (23).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These indicators included``discriminated against while eating meals with family members,''``neglected by family members,''`n eglected by neighbors,''``neglected in the workplace,'' and``facing problems in taking part in social programs'' and were experienced by 51.4z, 15.4z, 45.9z, 61.9z, and 79.5z of patients, respectively. A study conducted in Thailand considered similar indicators and found that approximately 40.0z of patients could not eat meals with their families (15), which was a similar proportion to that observed in the present study. Another study conducted in Nepal found that 43.3z of TB patients were neglected by others, and 36.7z were asked to stay away from work (23).…”
Section: Discussionsupporting
confidence: 89%
“…Two decades into the TB pandemic, stigma remains a significant challenge for TB control programs across the prevention-to-care continuum. In Bangladesh and many other developing countries, TB-related stigma has been introduced at different levels (11,12,(14)(15)(16)(17). Studies conducted in various countries have reported that stigma affecting TB patients is influenced by several socioeconomic variables (18).…”
Section: Introductionmentioning
confidence: 99%
“…9,10,[25][26][27]30,31,34,35,[37][38][39][40]42,49,55,58,71,[74][75][76][77][78] Patients with TB often consult traditional healers in Gambia, 74 South Africa, 40 Uganda, 10 Thailand, 77 Malaysia 76 and the Philippines. 78 Traditional herbal medicine is used by Samoans in the United States.…”
Section: Treatment and Health Responses To Tuberculosismentioning
confidence: 99%
“…Poverty predisposes individuals to TB through multiple mechanisms, such as malnutrition (Rocha et al 2011, Cegielski & McMurray 2004, and TB worsens poverty as it increases expenses and reduces income (Rocha et al 2011, Kemp et al 2007, Lonnroth et al 2007, Rajeswari et al 1999. Furthermore, poor TB-affected households often experience stigmatization; adding barriers to TB control (Rocha et al 2011, Atre et al 2011, Dhingra & Khan 2010, Pungrassami et al 2010, Jittimanee et al 2009. Poor people at the greatest risk of TB are therefore, in many settings, also the least able to access TB care (Rocha et al 2011).…”
Section: Social Network In Tuberculosismentioning
confidence: 99%